Perception Towards A Pplication Of Green Rooftop And Vertical Landscape Among Professionals And The Public In Tehran City, Iran - Taheri, Mohammah Reza (2008)
The high temperature during the hot season in Iran is the greatest challenge in cooling down residential and commercial buildings in cities because heating and cooling consume the highest amount of energy at the expense of environmental quality. Air pollution, urban heat effect and heat waves, peak energy demands, lack of green space are amongst the most critical environmental issues in Iranian urban areas especially in Tehran. The study implemented a humanistic approach integrated in a qualitative research methodology to develop a green roof strategy for Iran from amongst professional experts and public responses for reducing the high temperature. This study used. in-depth interviews among professionals and public about their perception towards the application of green roof policy and planning, and their related technical: and vertical landscape. Among the factors interviewed include the development of a localized green roof policy, consideration of different weather conditions, adaptation of new irrigation and water supply technologies, selection of plant species, certification, development of an education awareness program, and mitigation of high capital investment.